Anansi and the Bag of Wisdom - Retold by Sims, Lesley (London Usborne Publishing, 2011)
Anansi, King of the Spiders, is given a bag of wisdom to share but selfishly decides to keep it to himself. But can he carry it up to his secret hiding place without dropping it?
Include Color Illustrations
Keywords: Africa